A systematic review on the associations between built environment and mental health among older people - Chen, Yongkang; Xu, Lizhen; Cui, Xiangfen; Yang, Haoran; Liu, Yiling; Gao, Xin; Huang, Jianhong (Frontiers in Public Health, 2025)
IntroductionNumerous studies have examined the intricate correlation between community and residential environments, and their impact on health outcomes. However, the influence of built environment (BE) factors on the mental well-being of older individuals varies across different geographical regions.MethodsThis comprehensive systematic review synthesizes research on the association between BE elements and the mental health (MH) of the older adult population. A pool of 2938 studies were reviewed, with 21 studies meeting the inclusion criteria: 17 cross-sectional studies and 4 longitudinal studies.ResultsMost of these investigations were conducted in Asian countries and published within the last five years. The findings reveal that the GDS-15 scale is the most commonly used tool for assessing MH outcomes. We have established a quantifiable evaluation framework for BE elements, addressing the limitations of previous studies that relied on subjective perception measurements. Furthermore, a higher proportion of green spaces, improved facility accessibility, and shorter travel times and distances to destinations are positively linked with better MH of older adults.DiscussionWhile these associations are becoming increasingly evident, research on the effects of density, diversity, and design elements in relation to older adults’ MH remains limited and may varied significantly across different regions. Future research should focus on designing quasi-natural experimental studies to enhance our understanding of the convoluted and elaborate relationship between the BE and MH.